القيادة الواعية: دراسة نوعية لمؤشرات ممارسة القيادة الواعية لدى مديري المدارس الثانوية في جنوب الخليل/ فلسطين: القيادة الواعية لدي مديري المدارس - الطل, شادية يوسف; jondi, Nabil (Journal of College of Education, 2023)
This study aims to identify the evidences of conscious leadership practice among the South Hebron high school's principals. The study based on the qualitative approach and has employed the semi-open interview method. The interview included four - intensive questions to achieve the objective of this study. It has depended on the "Ground Theory" methodology to analyze the results. The researchers interviewed 10 schools' principals. The results of the participants' interviews revealed the following: Five dimensions of conscious leadership emerged, represented in self-awareness, awareness of others, cognitive awareness, situational awareness, and technical awareness. The study also revealed the importance of a conscious leader who can take care of the psychological and social factors of individuals and provide an incubating environment for them that enhances creativity and innovation. The study recommended increasing attention to necessity of conscious leadership and preparing the conscious leader who supports the idea of cooperation in work in an attempt to achieve the objectives of the corporation actively and efficiently.
Keywords: Conscious leadership, Awareness, Conscious leader, Hebron directorate, Secondary schools